Sounding the Alarm: Six Strategies for Medical Students to Champion Anti-Racism Advocacy - Fadoju D; Azap RA; Olayiwola JN (Dove Medical Press, 2021)
Deborah Fadoju,1,* Rosevine A Azap,1,* J Nwando Olayiwola2 1The Ohio State University College of Medicine, Columbus, OH, USA; 2Department of Family and Community Medicine, The Ohio State University College of Medicine, Columbus, OH, USA*These authors contributed equally to this workCorrespondence: J Nwando Olayiwola Email Nwando.Olayiwola@osumc.eduAbstract: Every year, incoming medical students take the Hippocratic Oath and pledge that they: “will be an advocate for patients in need and strive for justice in the care of the sick,” yet guidance on how to engage in community and public health advocacy is not a mandatory component of medical education. Therefore, students often feel insufficiently qualified to engage in advocacy efforts. As the nation has struggled with a viral pandemic (COVID-19) and witnessed an uprising against anti-Black racism and police brutality, it became immediately apparent that activism that marries medicine to anti-racism advocacy was needed. Further, we deduced that anti-racism activism at medical institutions would need to position medical students, often low in the medical hierarchy, as essential to the response. With the support of our leaders and mentors, we created a concerted series of strategies for medical students to become front and center in advocacy efforts. In this paper, we outline six strategies for medical students across the nation to champion anti-racism advocacy, based on our successful experiences in Central Ohio. This approach may have utility for other medical schools across the nation. These strategies include: embracing a common agenda; establishing formal structures; engaging affinity groups and allies; endorsing legislative advocacy; encouraging curricular reform; and enriching the pipeline. It is our hope that medical students will feel empowered and activated to lead and organize “good trouble” efforts that will ultimately improve the lives and health of the communities and patients they are being trained to serve.Keywords: racism, anti-racism, advocacy, medical education, community organizing, health equity